Impact of preoperative evaluation of tumour grade by core needle biopsy on clinical risk assessment and patient selection for adjuvant systemic treatment in breast cancer. Issue 9 (16th June 2015) - Waaijer, L; Willems, S M; Verkooijen, H M; Buck, D B; van der Pol, C C; van Diest, P J; Witkamp, A J
Abstract: Background: Histological characteristics are important when making a decision on adjuvant systemic treatment in breast cancer. Preoperative assessments of core needle biopsy (CNB) specimens are becoming increasingly relevant as novel minimally invasive ablative techniques are introduced, because a surgical specimen is no longer obtained with these methods. The clinical impact of potential underestimation of tumour grade on preoperative CNB on clinical decision-making was evaluated. Methods: Histological tumour grade was reassessed on CNB and resection specimens from consecutive invasive ductal carcinomas diagnosed between 2010 and 2013. For each patient, the indication for systemic therapy was assessed, based on either CNB or surgical excision, in combination with clinical characteristics and imaging findings. The clinical impact of discordance between tumour grade on CNB versus the resection specimen was assessed. Results: The analysis included 213 invasive ductal carcinomas in 199 patients. Discordance in tumour grade between CNB and the resection specimen was observed in 64 (30·0 per cent) of 213 tumours (κ = 0·53, 95 per cent c.i. 0·43 to 0·63). A decision on adjuvant treatment based on CNB would have resulted in overtreatment in seven (3·5 per cent) and undertreatment in three (1·5 per cent) of 199 patients. In the undertreated patients, incorrect omission of adjuvant systemic treatment would have increased the predicted 10-year mortality rate by 2·6–5·2 per cent and 10-year recurrence rate by 8·2–15·3 per cent based on the online risk assessment tool Adjuvant! Conclusion: The substantial discordance in tumour grading between CNB and resection specimens from breast cancer affects the indication for adjuvant therapy in only a small minority of patients with invasive ductal carcinoma. Assessment of tumour grade by CNB is feasible and accurate for the planning of postoperative treatment. Abstract : Discordance without clinical impact